Einige Fragen der Geometrie des metrischen Raumes von Hyperebenenelementen - Medviedevaitė, I. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. Х. Медведевайте. Некоторые вопросы геометрии метрического пространства гиперплоских элементов I. Medviedevaitė. Metrinės hiperplokšluminių elementų erdvės geometrijos klausimu